The Relationship of Tinnitus Distress With Personality Traits: A Systematic Review - van Munster, Juliëtte J. C. M.; van der Valk, Wouter H.; Stegeman, Inge; Lieftink, Arno F.; Smit, Adriana L. (Frontiers in Neurology, 2020)
Objectives: An association between tinnitus distress with anxiety and depression is described in literature. A similar relationship might exist between tinnitus distress and personality traits, especially since associations between personality traits and other chronic diseases are already revealed. In this systematic review, we aim to investigate whether personality is a risk factor for tinnitus distress. Design: We searched PubMed and EMBASE databases from inception up to December 31, 2018 for articles on the association between tinnitus distress and personality. Two researchers screened titles, abstracts and full texts for eligibility. Directness of evidence and risk of bias were assessed. From the included studies, study characteristics and outcome data of tinnitus distress and personality traits were extracted. Results: A total of 442 unique articles were screened of which 11 cross-sectional studies were eligible for critical appraisal and were used for data extraction. Including study populations were heterogenous and studies scored high to moderate risk of bias. 9 out of 11 articles showed an association between tinnitus distress and the personality of neuroticism. Conclusions: By limitations in the methodology of included studies, the evidence on specific personality traits as a risk factor for tinnitus distress, is inconclusive. Some evidence on a positive association with neuroticism is identified. To draw conclusions about causal relations, these further studies should be of longitudinal design in a cohort setting. These studies should assess tinnitus distress using validated questionnaires with multiple personality dimensions and validated questionnaires to assess personality traits.